A Novel Treatment of Acne Vulgaris Using a 1927 nm Fractional Thulium Laser: A Case Series - Chun SI (Dove Medical Press, 2024)
Soo Il Chun Chun Aesthetic and Laser Clinic, Seoul, South KoreaCorrespondence: Soo Il Chun, Chun Aesthetic and Laser Clinic, 91-2, Geumnanghwa-ro, Gangseo-gu, Seoul, Republic of Korea, Tel +82106267 8847, Email chun21@netsgo.comBackground and Aims: Acne vulgaris remains one of the most common and problematic dermatological conditions. Recently, a fractional 1927 nm thulium laser has been developed with specific water absorption characteristics which may be of interest in the treatment of acne.Subjects and Methods: Nine consecutive Korean subjects, 6 females and 3 males, ages ranging from 13 to 33 yr, presented with a mixture of inflammatory and noninflammatory acne. Baseline clinical photography, image analysis and lesion counts were performed. A fractional 1927 nm thulium laser (FTL) delivered 6 treatment sessions in 5 subjects and 5 sessions in 4 subjects, 4 weeks between sessions. Pain during treatment was assessed. At 32 weeks after the last treatment session, an independent Investigator Global Assessment (IGA) performed lesion counts and graded the severity of the acne at baseline and the final assessment on a quintile scale. Data were analyzed statistically.Results: All 9 subjects completed the study with significant reductions in the inflammatory and noninflammatory lesions (P values 0.0012 and 0.0081, respectively) with overall lesion counts at the final assessment ranging from 60% to 97.1%, and acne grades in the IGA dropping by an average of 1.67 (range 1 to 3 grades). There was no significant difference in lesion counts or acne grades between the subjects who had 6 treatments and those who had 5 (P = 0.7695). Mild pain was reported during treatment, and no adverse events were reported by either the subjects or investigator.Conclusions: The FTL at the parameters used in the present study caused disruption to the upper portion of the affected follicles and sebaceous glands under an intact stratum corneum, thereby destroying or damaging the causative Cutibacterium acnes. The superficial controlled coagulation additionally induced follicular remodeling and tissue regeneration, potentially contributing to the noticeable results in inflammatory and noninflammatory acne lesions.Keywords: Cutibacterium acnes, thulium laser, infundibulum, sebaceous glands, follicular remodeling, selective photothermolysis